Healthcare disparities at the crossroads with healthcare reform - Williams, Richard Allen 1936-.; SpringerLink (Online service). (New York Springer, 2011)
Building upon the success of Dr. Williams's widely influential book Eliminating Healthcare Disparities in America: Beyond the IOM Report, this new volume takes a fresh and timely look at the state of healthcare reform and the progress and problems we face in the pursuit of healthcare equality. This book focuses on how the elimination of disparities can be accomplished through targeted efforts made within the context of reform. Comprising the combined efforts of the nation's best health policy analysts, researchers, key opinion leaders and clinicians, this book addresses both current and impending legislation and future movements in healthcare. With the knowledge that the problem of disparities extends beyond the present political arena into the larger scope of all aspects of healthcare delivery, the authors provide critical analysis of the causation of disparities, insightful examples of what has worked, and a striking call to action with implementable strategies for advancing equality.
The Potential Impact of Performance Incentive Programs on Racial Disparities in Health Care -- Eliminating Disparities in Health Care Through Quality Improvement -- Monitoring Socioeconomic Determinants for Healthcare Disparities: Tools from the Public Health Disparities Geocoding Project -- Perspective: Title VI, Healthcare Reform, and the Need for a State Antidiscrimination Law -- Quality of Care and Health Disparities: The Evolving Role of the Government -- The Association of Black Cardiologists: A Small-Group Success Story in Addressing Healthcare Disparities -- Breathing Easier in Seattle: Addressing Asthma Disparities Through Healthier Housing -- Breast and Prostate Cancer Healthcare Disparities -- The Role of Health IT in Eliminating Health Disparities -- Remote Area Medicalª: Pioneers of No-Cost Health Care -- Principles for Eliminating Racial and Ethnic Disparities in Health Care Under Healthcare Reform.
Electronic reproduction.
Keywords: Health services accessibility -- United States; Equality -- Health aspects -- United States; Medical policy -- Social aspects -- United States; Medical care -- Needs assessment -- United States; Health care reform -- United States; Electronic books